2018
DOI: 10.1161/circulationaha.118.034818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacubitril/Valsartan Versus Irbesartan in Patients With Chronic Kidney Disease

Abstract: URL: http://www.isrctn.com . Unique identifier: ISRCTN11958993.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
151
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(162 citation statements)
references
References 46 publications
4
151
2
5
Order By: Relevance
“…4 The tolerability and safety profiles of the two treatments were not different. The UK HARP-III trial (United Kingdom Heart and Renal Protection-III) has demonstrated that, in a wide range of people with proteinuric chronic kidney disease, adding neprilysin inhibition to angiotensin II receptor blockade has no additional effect on kidney function or albuminuria compared with irbesartan.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…4 The tolerability and safety profiles of the two treatments were not different. The UK HARP-III trial (United Kingdom Heart and Renal Protection-III) has demonstrated that, in a wide range of people with proteinuric chronic kidney disease, adding neprilysin inhibition to angiotensin II receptor blockade has no additional effect on kidney function or albuminuria compared with irbesartan.…”
Section: Discussionmentioning
confidence: 94%
“…The UK HARP-III trial (United Kingdom Heart and Renal Protection-III) has demonstrated that, in a wide range of people with proteinuric chronic kidney disease, adding neprilysin inhibition to angiotensin II receptor blockade has no additional effect on kidney function or albuminuria compared with irbesartan. 4 The tolerability and safety profiles of the two treatments were not different. However, compared with irbesartan, sacubitril/valsartan further reduces both blood pressure and biomarkers of cardiovascular risk (Troponin I and N-terminal pro-B-type natriuretic peptide) and raises the hypothesis that ARNI could reduce cardiovascular morbidity and mortality in a heart failure population with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, renal adverse events are observed frequently during clinical practice, when treating patients with angiotensin‐converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) 5 . Neprilysin (NEP or neutral endopeptidase) is the enzyme responsible for the degradation of natriuretic peptides (NPs), as well as other mediators, such as bradykinin or adrenomedullin 6‐8 . Neprilysin inhibition (NEPi) is capable of activating RAS without breaking down angiotensin II or altering blood pressure (BP).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…It also has been shown the weak correlation with BUN and no correlation with Scr, eGFR-MDRD for early diagnosis of DN, and the results are consistant with the past finding. 12 And indicated the decreased BF and prolong MTT in the CT perfusion imaging of early DN, and reflected the increase of renal artery resistance, the changes of renal artery morphology and renal cortex perfusion, and the evaluation of glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that the renal cortex and medulla blood flow perfusion are damaged in hypertensive and diabetic nephropathy renal altered function, and the amount of blood perfusion of renal cortex is a direct index to judge the renal blood flow [12]. CT perfusion imaging was a proposed method in the early 90th century, and it can evaluate accurately renal function for clinical reference with clear anatomical image.…”
Section: Discussionmentioning
confidence: 99%